Facile preparation and performance of hierarchical self-assembly MnCo2O4 nanoflakes as anode active material for lithium ion batteries. (20th October 2015) - Zhang, Youwei; Wang, Xianyou; Zhao, Qinglan; Fu, Yanqing; Wang, Hao; Shu, Hongbo
Abstract: Hierarchical self-assembly MnCo2 O4 nanoflakes with size of about 4 μm as anode active material for Li-ion batteries (LIBs) have been prepared by a facile method. The structure and physicochemical properties of the as-prepared self-assembly MnCo2 O4 nanoflakes are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), nitrogen adsorption-desorption isotherm, cyclic voltammogram (CV) and galvanostatic discharge-charge tests. The results show that the as-prepared self-assembly MnCo2 O4 nanoflakes display a novel multi-lamellar macrostructure with a large number of well-distributed pores. The specific surface area of the as-prepared MnCo2 O4 is about 49.44 m 2  g −1 and the average pore size is about 2.34 nm. In addition, due to the hierarchical self-assembly structure, the MnCo2 O4 nanoflakes exhibit an enhanced lithium storage capacity and excellent cycling stability (925 mAh g −1 at a current density of 100 mA g −1 after 50 cycles). More importantly, it can render the reversible capacity of 719 mAh g −1 after 50 cycles, even at a high current density of 400 mA g −1, indicating its potential for high power LIB applications.